PENERAPAN METODE QAWA'ID WA TARJAMAH BERBASIS PENDEKATAN STUDENT CENTERED LEARNING (SCL) PADA PEMBELAJARAN QIRA’AH MUWASSA’AH DI IAI SUNAN KALIJAGA MALANG: APPLICATION OF QAWA'ID WA TARJAMAH METHOD BASED ON STUDENT CENTERED LEARNING (SCL) APPROACH IN QIRA'AH MUWASSA'A LEARNING - Arif, Muhammad; M. Ainur Roziqi; Muhammad Bakhrul Ilmi (Lisanul Arab: Journal of Arabic Learning and Teaching, 2025)
This study aims to analyze the application of the Qawa'id wa Tarjamah method based on the Student-Centered Learning (SCL) approach in teaching Qira'ah Muwassa'ah at the Sunan Kalijaga Islamic Institute (IAI) Malang. The research method used is qualitative with a descriptive analysis type, focusing on the learning process and the effectiveness of this method in improving reading skills and understanding of Arabic texts. The research data were obtained through observation, interviews, and documentation, and then analyzed inductively. The results of the study indicate that the application of the Qawa'id wa Tarjamah method combined with the SCL approach can increase students' active participation in the learning process. Students not only understand Arabic grammar theoretically but can also apply it in a broader reading context. In addition, the SCL approach encourages more interactive, creative, and collaborative learning, making the classroom atmosphere more dynamic and conducive. This study concludes that the integration of the Qawa'id wa Tarjamah method with the Student-Centered Learning approach has proven effective in improving students' reading competence in Qira'ah Muwassa'ah learning.